Detection of Toxoplasma gondii in domestic birds in middle Euphrates region of Iraq by using poltmerase chain reaction technique - Hadi M. Hamza et.al (Al-Qadisiyah Journal of Pure Science, 2017)
The current study was conducted to detection the Toxoplasma gondii in five species of avian including , Gallus gallus domesticus , Meleagris galbpavol , Anser anser , Anasplatyrhychos domesticus and Columba livia in middle Euphrates province of Iraq ,during 2012-2013 by using conventional Polymerase Chain Reaction to detect of B1 gene which was specific gene of T.gondii in blood samples of avian . A total of 400 Avian , collected , including 80 samples of each species (20 samples of chicken , Turkey , geese , and Ducks) of each province of middle Euphrates (AL-Diwania , Babylon , AL-Najaf and Karbala) in addition to 80 samples of pigeons from the center of AL-Diwania province.The results of 400 blood samples of avian were showed there were 38 samples (%9.5) gave positive result , include ,14 (% 17.5) from chicken , 12 (%15) from Turkey , 8 (%10) from geese , 4 (%5) from pigeon ,whereas the results were showed the B1 gene was not present in the blood samples of ducks and .the highest percentage was recorded in chicken %17.5,whereas the lowest percentages were %5 in pigeon.Also the results were showed the percentage of four types of avian (except pigeons ) according to the provinces were, the percentages were %16.25(High percentage) , %5 (Low percentage) ,% 6.25 ,% 15 in Karbala, AL-Najaf AL-Diwania , Babylon province. The results showed ,the percentage of infection in the samples areas were highest(%17.5) whereas in the urban areas were lowest (%12.5) polymerase chain reaction.